2020
DOI: 10.1038/s41598-020-74583-y
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of atherosclerotic plaque growth using computational biomechanics and patient-specific data

Abstract: Atherosclerosis is the one of the major causes of mortality worldwide, urging the need for prevention strategies. In this work, a novel computational model is developed, which is used for simulation of plaque growth to 94 realistic 3D reconstructed coronary arteries. This model considers several factors of the atherosclerotic process even mechanical factors such as the effect of endothelial shear stress, responsible for the initiation of atherosclerosis, and biological factors such as the accumulation of low a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…As a result, an area with low values of wall shear stress (WSS), which is a hemodynamic parameter directly related to endothelial function and atherosclerosis, will appear in the distal segment of the plaque, accelerating the plaque growth (Liu et al, 2018;Arzani, 2020). In a study on 900 artery segments extracted from 94 patient-specific coronary arteries, Pleouras et al found that the plaque growth and degree of stenosis predicted using the baseline WSS values derived from computational simulation were in accordance with the follow-up clinical observation (Pleouras et al, 2020b). Therefore, the plaque geometry can influence the plaque growth by hemodynamic effects in pathological mechanisms, which contributes to the geometric consistency of different coronary plaques.…”
Section: Discussionmentioning
confidence: 87%
“…As a result, an area with low values of wall shear stress (WSS), which is a hemodynamic parameter directly related to endothelial function and atherosclerosis, will appear in the distal segment of the plaque, accelerating the plaque growth (Liu et al, 2018;Arzani, 2020). In a study on 900 artery segments extracted from 94 patient-specific coronary arteries, Pleouras et al found that the plaque growth and degree of stenosis predicted using the baseline WSS values derived from computational simulation were in accordance with the follow-up clinical observation (Pleouras et al, 2020b). Therefore, the plaque geometry can influence the plaque growth by hemodynamic effects in pathological mechanisms, which contributes to the geometric consistency of different coronary plaques.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, for a more exhaustive vision related to the modeling of vascular adaptation, the reader should be directed also to multiscale frameworks entirely based on continuum models (which are not the object of this review), implying that also the cell scale is represented through ODE/PDE systems. Examples can be found in models of atherosclerosis (e.g., Cilla et al (2014) , Di Tomaso et al (2015) , Thon et al (2018) and Pleouras et al (2020) ), ISR (e.g., Lally and Prendergast (2006) , Escuer et al (2019) and Maes et al (2021) ), vein graft remodeling (e.g., Budu-Grajdeanu et al (2008) and Casarin et al (2017) ) and other vascular applications (see Humphrey (2021) for an extensive review on constrained mixture models of tissue growth and remodeling). The difference of these works with those reviewed in Multiscale Agent-Based Modeling Frameworks of Vascular Pathophysiology mainly regarded the representation of the cell scale (through a ODE/PDE versus ABM approach), which thus determined the nature of the multiscale framework to be either hybrid (i.e., based on the combination of continuum models with an ABM) or fully-continuum.…”
Section: Agent- Versus Continuum-based Multiscale Framework: Strengths and Limitationsmentioning
confidence: 99%
“…Besides the works by Casarin et al (2017) and Maes et al (2021) , in which a set of ODEs was adopted to describe the temporal dynamics of tissue growth and remodeling, in all the other cited continuum-based studies PDE systems were implemented to capture the spatio-temporal evolution of the species of interest (e.g., growth factors, cells, ECM components, LDL), and thus the subsequent tissue remodeling, in response to fluid or mechanical stimuli. For example, in the patient-specific atherosclerosis model by Pleouras et al (2020) , CFD simulations were coupled with a PDE system describing mass transport of monocytes, LDL, and high-density lipoproteins, and inflammatory species’ dynamics in the arterial wall, ultimately leading to plaque growth over time ( Figure 11 ). The model predictions well replicated the in-vivo follow-ups in terms of plaque growth and lumen area reduction (accuracy of about 80%), thus supporting the potentialities of the proposed framework.…”
Section: Agent- Versus Continuum-based Multiscale Framework: Strengths and Limitationsmentioning
confidence: 99%
“…Our approach is aiming to the utilization of a plaque growth model (20,21) which is used for the simulation of coronary arterial disease progress in human data with the potential to predict atheromatic areas of risk. The development of this model requires the proper definition of the equations that define the biologic processes responsible for atherosclerosis, using the state-of-the-art models, but also the latest available in literature experimental data.…”
Section: Virtual Arterial Geometries Generationmentioning
confidence: 99%
“…The employed model has been previously validated and it can be used to simulate the plaque growth and lumen narrowing of 3D reconstructed coronary arteries (20). For this purpose, a multi-level approach is implemented.…”
Section: Virtual Arterial Geometries Generationmentioning
confidence: 99%